2006
DOI: 10.1111/j.1600-079x.2006.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against oxidative damage and restores expression of GLUT4 gene in the hyperthyroid rat heart

Abstract: To understand the mechanism of cardiovascular dysfunction in the hyperthyroid condition, the role of oxidative stress was examined in rats treated with 3,5,3'-triiodo-l-thyronine (T3). Treatment of rats daily with T3 (8 microg/100 g BW) for 15 days resulted in an increase in heart weight to body weight ratio, which was ameliorated by antioxidants, melatonin (2 mg/100 g BW) or vitamin E (4 mg/100 g BW). Both melatonin and vitamin E also inhibited rises of lipid peroxidation and hydroxyl radical generation and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 67 publications
1
57
1
4
Order By: Relevance
“…Although melatonin was suggested to have some antiremodelling potential [6] and was shown to prevent cardiac hypertrophy, to reduce oxidative load and to alter the expression of metabolically important genes in the hyperthyroid rat [23], in our study melatonin failed to prevent LVH induced by L-NAME. Some studies have suggested that NO delivery might attenuate LVH independently of blood pressure reduction [24], whereas others have indicated that the haemodynamic load may be the major determinant of LVH, and neurohumoral activation including NO may play a rather modulatory role [13,25].…”
Section: Discussioncontrasting
confidence: 71%
“…Although melatonin was suggested to have some antiremodelling potential [6] and was shown to prevent cardiac hypertrophy, to reduce oxidative load and to alter the expression of metabolically important genes in the hyperthyroid rat [23], in our study melatonin failed to prevent LVH induced by L-NAME. Some studies have suggested that NO delivery might attenuate LVH independently of blood pressure reduction [24], whereas others have indicated that the haemodynamic load may be the major determinant of LVH, and neurohumoral activation including NO may play a rather modulatory role [13,25].…”
Section: Discussioncontrasting
confidence: 71%
“…Excess T 3 induces a hypermetabolic state in the heart and also increases cellular respiration leading to increased ROS production, which is not completely neutralized by the cellular antioxidants, and there is gradual and progressive accumulation of ROS in cardiomyocytes (Ghosh et al 2007, Abel & Doenst 2011. This is evident from increased lipid peroxidation and depletion of cellular antioxidants seen after 15 days of T 3 treatment ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Lipid peroxides in the cell-free homogenate obtained from LV tissue were determined as described earlier (Ghosh et al 2007). Briefly, LV tissue (200 mg) was homogenized in ice-cold 0.9% saline (pH 7.0) with a Potter-Elvehjem glass homogenizer for 30 s. The homogenate was centrifuged at 800 g for 3 min at 4 8C and the cell-free homogenate was mixed with thiobarbituric acid (TBA)-trichloro acetic acid reagent with thorough shaking.…”
Section: Determination Of Lipid Peroxidationmentioning
confidence: 99%
“…The lipid peroxides in the homogenate was determined as thiobarbituric acid reactive substances (TBARS) by previously described method [33,34]. Briefly, the homogenate was mixed with TBA-TCA (Thiobarbituric acidTrichloro acetic acid) reagent with thorough shaking and boiled for 15 min in a boiling water bath.…”
Section: Determination Of Lipid Peroxidation In Cardiac Tissuementioning
confidence: 99%